Research Of The Work Of The System "Base - Foundation With A Damping Layer-Building" On An Inhomogene Soil Base - et. al., Makhmudov Said Makhmudovich, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An engineering technique has been developed that allows calculating the interactions between the structure of the beam foundation when constructing the upper and lower beams, the parameters of the damping layer from the condition of controlled loading of the foundation, or the stress-strain state of the system "base - foundation with a damping layer - building". An example of calculating a damping layer in accordance with the developed methodology is given, as well as a comparison of the results of an engineering and numerical solution, and a good convergence of the results is obtained.